Body Mass Index Trajectories From Birth to Midlife and Vertebral Dimensions in Midlife: the Northern Finland Birth Cohort 1966 Study. (17th July 2018) - Oura, Petteri; Junno, Juho‐Antti; Auvinen, Juha; Niinimäki, Jaakko; Karppinen, Jaro; Ojaniemi, Marja; Paananen, Markus
Abstract: Vertebral fracture risk is higher among individuals with small vertebral dimensions. Obesity is a global health problem and may also contribute to bone size and fracture risk. In this work we report the association between life course body mass index (BMI) and vertebral cross‐sectional area (CSA) in midlife. The Northern Finland Birth Cohort 1966 study with its 46‐year follow‐up provided the material for this study. A subsample of 780 individuals had attended lumbar magnetic resonance imaging (MRI) at the age of 46 years, and had records of objectively measured BMI from the ages of 0, 7, 15, 31, and 46 years. Of these, MRI‐derived data on vertebral size was available for 682 individuals. We identified latent lifelong BMI trajectories by performing latent class growth modeling (LCGM) on the BMI data, and then used sex‐stratified linear regression models to compare the identified trajectory groups in terms of midlife vertebral CSA. Gestational age, education years, adult height, lifelong physical activity, lifelong smoking history, and adulthood diet were assessed as potential confounders. Three distinct trajectory groups ("stable slim, " "stable average, " and "early onset overweight") were identified among both sexes. Comparisons to the stable slim trajectory revealed that vertebral CSA was significantly ( p  < 0.001) larger among the stable average and early onset overweight trajectories (69.8 and 118.6 mm 2 larger among men, 57.7 and 106.1 mm 2 larger among women, respectively). We conclude that lifelong BMI has a positive association with midlife vertebral size among both sexes. Future studies should characterize the mediating factors of this association. © 2018 American Society for Bone and Mineral Research